Livro sobre nada: poética em pedaços de quase instante - Costa, Valdegilson da Silva (2021)
The research proposed here about Livro sobre nada (1996), by Manoel de Barros, aims to evalute the aesthetic effects resulting from the mobilization in space and time, from the perspective of the perspective of the challenging character the Barrean writing estabilishes with teh conventional temporality and spatiality, marked by the incessant utilitarianism and the ininterrupted informational load - characteristic of modernity. In this sense, our research problematizes, in a more specific way, the literary procedures adopted by Manoel de Barros to promote the spatiotemporal displacements in Livro sobre nada (1996), which is analyzed from the perpective of the Phenomenology proposed by Maurice Merleau-Ponty (2018). Our hypothesis sees, in Barrean poetry trangressive elements to a perception baseado n isiolacionism, since the relatioship between the lyrical selves in question, objects and beings mobilize this poetic, which lodges and moves in a multiple temporality, according to the Heideggerian concept of ekstases. From this perspective, poetry is an event and a constant unhappiness, phenomenon investigated according to the concept of literary space, proposed by Maurice Blanchot (2005), of inoperability, originating from Giorgio Agamben (2018), as well as literary landscape, whose reference will be the ideas of Michell Collot (2013). The authour’s aesthetic awareness creates na order that results in numerous poems of a metalinguistic character, analyzed from excerpts from interviews given by the poet himself, from the propositions of Samira Chalhub (1988) and María Zambrano (1966), whom we will resort as a contribution about the relationship between poetry and thought